MAHYIDDIN DODENT: TOKOH PARIWISATA KOTA SABANG (1952-2013) - ATHIT MUSNANDAR; Teuku Abdullah; Anwar Yoesoef (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2018)
ABSTRACTThe research entitled "Mahyiddin Dodent, Tourism Prominent of Sabang City 1952-2011" raises the question of how the life journey of Mahyiddin Dodent becomes a tourism character who has great influence in the city of Sabang. This study aims to (1) know the biography of Mahyiddin Dodent's life, and (2) to know the role of Mahyiddin Dodent in Sabang City, 1952-2011. This study uses a qualitative approach and historical method that consists of five steps namely the selection of themes, heuristics, verification, interpretation and historiography. Technique of collecting data is done by interview, documentation, observation and literature study. The research results can be known that Mahyiddin Dodent is a tourism figure in the 1980s, where he only took the school level education (SR). Mahyiddin Dodent gained knowledge of the ocean from experience during wandering.Mahyiddin Dodent's important role is to make Sabang as a tourist attraction, especially characterized by the conservation of coral reefs and opposed the illegal activities of the fisherman's illegal fishing. Conservation of Mahyiddin Dodent coral reef is intended to be a tourist attraction. On this struggle Mahyiddin Dodent won Kalpataru award from President Susilo Bambang Yudoyono in 2010.Keyword: Mahyiddin Dodent, Tourism Character, Sabang City.